2015
DOI: 10.2807/1560-7917.es.2015.20.46.30067
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of invasive meticillin-resistant Staphylococcus aureus infections in Germany, 2010 to 2014

Abstract: Voluntary surveillance systems in Germany suggest a recent decline in the incidence of infections (subsequent to at least 2010) with meticillin-resistant Staphylococcus aureus (MRSA) from various types of specimens and settings. We asked whether this decline is reflected by data from the mandatory national surveillance system for invasive MRSA infections. Our analysis is based on the population in Germany in 2010 to 2014. Cases were identified from passive reporting by microbiological laboratories of the diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…Our data are also consistent with previous analyses that have indicated declines in MRSA in the hospital setting and for invasive infections [ 1 – 3 ], with the previous analysis of ARS data from outpatient setting [ 5 ] and indirectly also with data from the national reference laboratory that suggest low levels of LA- and CA-MRSA in Germany [ 6 , 9 ]. Therefore, they indicate a general decline in MRSA-infection in Germany in all settings and for all sample types.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our data are also consistent with previous analyses that have indicated declines in MRSA in the hospital setting and for invasive infections [ 1 – 3 ], with the previous analysis of ARS data from outpatient setting [ 5 ] and indirectly also with data from the national reference laboratory that suggest low levels of LA- and CA-MRSA in Germany [ 6 , 9 ]. Therefore, they indicate a general decline in MRSA-infection in Germany in all settings and for all sample types.…”
Section: Discussionsupporting
confidence: 92%
“…The incidence of infections with methicillin resistant Staphylococcus aureus (MRSA) is thought to be on the decline in Germany. This is corroborated by data from the national mandatory reporting system [ 1 ], from a hospital surveillance system [ 2 ], from surveys [ 3 ] and from analysis of data submitted to the European Antimicrobial Resistance Surveillance Network [ 4 ]. However, these analyses rely on invasive samples or on samples from hospitals only.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…Since their emergence in the 1960s, methicillin-resistant Staphylococcus aureus (MRSA) infections have been a major health care concern worldwide ( Chen & Huang, 2014 ; Walter et al, 2015 ; Wang et al, 2010 ). Many epidemiological studies have revealed that different multilocus sequence types (MLST) present specific characteristics such as virulence gene profiles ( Recker et al, 2017 ; Schuenck et al, 2012 ; Wang et al, 2009 , 2010 , 2012 ).…”
Section: Introductionmentioning
confidence: 99%